THE SIGNIFIER AND THE SIGNIFIED (Journal of Foreign Language Studies, 2019)
The article analyzes F. de Saussure’s opinion on the signifier and signified. In French, he calls the signifier ‘signifiant’ and the signified ‘signifié’, which is a sound-image and a concept or sense of a linguistic unit, respectively. The writer of this article criticizes the opinion and clarifies the signifier and signified in linguistics so as to distinguish the signified with the sense of a linguistic unit.
Keywords: the signifier; the signified; sense; form; referent; phonetic word